RURAL AREAS DEVELOPMENT PROBLEMS (DILAEMA) IN THEORY AND PRACTICE - Sawicka, Janina (Acta Scientiarum Polonorum. Oeconomia, 2002)
Polish economy nowadays, subjects to the threefold restructuring: globalisation, transformation process to the market ruls and as a preacession country must adopt to the European Union goals and institutions. The paper presents theoretical as well as practical aspects of rural development in Poland. Discussion on theory contains definitions of rural areas, their multifunctional and rural entrepreneurship development. Barriers and limitations to rural areas development and the assistans of public means supporting rural area development, were discussed.